2016
DOI: 10.1080/21645515.2015.1115934
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive safety assessment of a human inactivated diploid enterovirus 71 vaccine based on a phase III clinical trial

Abstract: Human enterovirus 71 (EV71) is a causative agent of hand, foot, and mouth disease (HFMD). In a previous phase III trial in children, a human diploid cell-based inactivated EV71 vaccine elicited EV71 specific immune responses and protection against EV71 associated HFMD. This study aimed to assess the factors influencing the severity of adverse events observed in this previous trial. This was a randomized, doubleblinded, placebo-controlled, phase III clinical trial of a human diploid vaccine carried out in 12,00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“… 22 Furthermore, a phase III clinical trial of inactivated diploid enterovirus has been reported to demonstrate satisfactory safety. 23 However, between 1986 and 2008, the full-length genomic sequence of Taiwan’s popular EV-A71 was internally and recombined, and dominant genotype changes from B to C or C to B occurred at least three times. 24 Subtypes of EV-A71 subtypes were observed over time, but most people did not know their appearance and extinction at the exact time.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Furthermore, a phase III clinical trial of inactivated diploid enterovirus has been reported to demonstrate satisfactory safety. 23 However, between 1986 and 2008, the full-length genomic sequence of Taiwan’s popular EV-A71 was internally and recombined, and dominant genotype changes from B to C or C to B occurred at least three times. 24 Subtypes of EV-A71 subtypes were observed over time, but most people did not know their appearance and extinction at the exact time.…”
Section: Discussionmentioning
confidence: 99%
“…2 EV71 and CVA16 are responsible for more than 90% of HFMD cases, and EV71 is responsible for most severe cases and deaths. 29 Three inactivated EV71 vaccines have shown protective efficacy in phase 3 clinical trials and been approved for commercialization in mainland China, [8][9][10]29 but the low production of inactivated EV71 means it is difficult to supply enough inactivated EV71 vaccines for nationwide or worldwide mass immunization of the at-risk populations at the outbreaks of EV71 HFMD. Pichia pastoris is a commonly used yeast expression system for recombinant proteins of interest and has many advantages in vaccine development, including low fermentation cost, high expression levels, and high-density growth in fermentation bioreactors.…”
Section: Discussionmentioning
confidence: 99%
“…Three inactivated EV71 vaccines had been proven to be effective for preventing EV71 infection in children and have been approved for marketing in mainland China, [8][9][10] however, these vaccines have some disadvantages such as potentially epitope-damaging, the risk of being inactivated incompletely and high production cost. 11 VLPs are considered a very attractive platform for viral vaccine development because of their high immunogenicity and excellent safety.…”
Section: Introductionmentioning
confidence: 99%